Barriers to Hepatitis C Treatment in HIV co-infected Patients in the Era of New Direct-Acting Antiviral Therapy. (4th October 2017) - Deering, Caytlin; Coppock, Dagan; Boyle, Suzanne; Szep, Zsofia; Franks, Taneesa; Scott, Tiffany; Kesaris, Anna; Chou, Edgar; Lee, Dong Heun
Abstract: Background: Hepatitis C virus (HCV) infection disproportionately affects HIV-infected patients. Co-infected patients have worse prognoses than mono-infected patients. HCV treatment with new oral direct acting antiviral (DAA) therapy is effective in HIV/HCV co-infected patients with cure rates similar to mono-infected patients. Despite the effective treatments, only a small proportion of co-infected patients are treated for HCV infection. This study aims to describe barriers to hepatitis C treatment in HIV/HCV co-infected patients. Methods: We performed a retrospective observational study of HIV/HCV co-infected patients seen at an urban HIV clinic in the year of 2016 at Drexel University, Philadelphia, PA. We compared patients who were treated for HCV infection vs. those who were untreated. We described demographics and barriers-to-care associated with untreated HCV infection. Results: Among 1322 patients seen, 112 patients had chronic HCV infection. The median age was 54 (IQR: 48–58) years old and two-thirds (78 (67.8%)) were African-American. Median CD4 counts were 515 (354–750), 85% had controlled viremia (VL < 200 copies) and 43 (44.3%) had fibrosis scores above F3. Sixty were treated for chronic HCV. Among the 55 untreated patients, 20 (36.4%) were in the process of evaluation, 11 (20%) had uncontrolled HIV viremia (HIV viral load >200 copies) and 9 (16.4%) were actively using illicit substances. In HCV treated vs. untreated patients, it was more common to have an undetectable viral load (60% vs. 40%); CD 4 count > 200 (58% vs. 42%); and absence of cocaine abuse (58% vs. 42%). Patients who completed HCV treatment had a higher rate of HCC screening (62% vs 33%, P = 0.005). Conclusion: Despite the availability of effective DAA therapy, only one half of co-infected patients were treated for HCV. The significant barriers in the delay of HCV treatment were uncontrolled HIV viremia and substance abuse. To overcome these barriers, we suggest: (1) providing support and resources to help patients cease cocaine use, (2) encourage frequent follow up with patients to achieve HIV suppression. This will improve access to treatment, decrease mortality, and improve the quality of life for this patient group. Disclosures: E. Chou, Gilead: Grant Investigator, Research grant; D. H. Lee, Gilead: Grant Investigator, Research grant